3D computational simulation and experimental characterization of polymeric stochastic network materials : case studies in reinforced eucalyptus office paper and nanofibrous materials - Curto, Joana Maria Rodrigues (2017)
Submitted by Helena Fortuna (hfortuna@ubi.pt) on 2017-04-19T15:57:42Z No. of bitstreams: 1 JC_PhD_Abril_2012_final.pdf: 3681188 bytes, checksum: 920c8158f549db4b08d3c32f5fd25239 (MD5)